Capital controls and the real exchange rate: Do controls promote disequilibria? - Juan Antonio Montecino (University of Massachusetts, Department of Economics, 2015)
The consensus view is that capital controls can effectively lengthen the maturity composition of capital inflows and increase the independence of monetary policy but are not generally effective at reducing net inflows and influencing the real exchange rate. This paper presents empirical evidence that although capital controls may not directly affect the long-run equilibrium level of the real exchange rate, they may enable disequilibria to persist for an extended period of time relative to the absence of controls. Allowing the speed of adjustment to vary according to the intensity of restrictions on capital flows, it is shown that the real exchange rate converges to its long-run level at significantly slower rates in countries with capital controls. This result holds whether permanent or episodic controls are considered. The benchmark estimated half-lives for the speed of adjustment are around 3.5 years for countries with strict capital controls but as low as 2 years in countries with no restrictions on international capital flows. The paper also presents a stylized two-sector dynamic investment model with constraints on externally-funded investment to illustrate potential theoretical channels.
Keywords: F2; F31; F36; F41; 330; Capital Controls; Real Exchange Rates; Undervaluation